Isolation, structure identification, and immunostimulatory effects in vitro and in vivo of polysaccharides from Onosma hookeri Clarke var. longiforum Duthie. (9th August 2022) - Wu, Qiang; Er‐bu, Aga; Liang, Xiaoxia; He, Changliang; Yin, Lizi; Xu, Funeng; Zou, Yuanfeng; Yin, Zhongqiong; Yue, Guizhou; Li, Lixia; Song, Xu; Tang, Huaqiao; et al.
Abstract: BACKGROUND: This study characterized an acidic polysaccharide ( OHC ‐LDPA) isolated from the medicinal and edible homologous plant Onosma hookeri Clarke var. longiforum Duthie. The structure of OHC ‐LDPA was elucidated based on the analysis of infrared, one‑/two‐dimensional nuclear magnetic resonance, and gas chromatography–mass spectrometry data. The immunostimulatory effects of OHC ‐LDPA were identified by both in vitro and in vivo models. RESULTS: The structure of OHC ‐LDPA was elucidated as a typical pectin polysaccharide, consisting of galacturonic acid, galactose, arabinose, and rhamnose as the primary sugars, with linear galacturonic acid as the main chain and arabinogalacturonic acid as the main branched components. OHC ‐LDPA could significantly stimulate the proliferation and phagocytosis of RAW264.7 macrophages and the release of nitric oxide in vitro . Also, it could accelerate the recovery of spleen and thymus indexes, enhance the splenic lymphocyte proliferation responses, and restore the levels of interleukin‐2, interleukin‐10, interferon‐ γ, and immunoglobulin G in the serum in a cyclophosphamide‐induced immunosuppressed‐mice model. In addition, OHC ‐LDPA could restore the intestinal mucosal immunity and reduce the inflammatory damage. CONCLUSION: OHC‐ LDPA could improve the immunity both in vitro and in vivo and could be used as a potential immunostimulant agent. © 2022 Society of Chemical Industry.